Epithelial Salivary Gland Tumors in Ahvaz, Southwest of Iran - Saede Atarbashi Moghadam; Fazele Atarbashi Moghadam; Mehdi Dadfar (Tabriz University of Medical Sciences, 2010)
Background and aims. Salivary gland tumors are rare and specific lesions. There are differences in the incidence and frequency of salivary tumors in both minor and major salivary glands in different countries. This study was carried out to determine the prevalence of major and minor salivary gland tumors in Ahvaz in the south of Iran. Materials and methods. All the cases, recorded in Imam Khomeyni Hospital and Shafa Hospital, Ahvaz, Iran from 1997 to 2008 were assessed. Age, gender, anatomical location, and histology of all the specimens were evaluated. Results. Of 112 cases, 84 cases were benign and 28 cases were malignant. Female predominance was observed in these cases. Most lesions appeared in the third to fifth decades of life (60.71%). The incidence of malignant salivary gland tumors increased with age and male predominance was found in malignant tumors. The majority of the tumors occurred in parotid gland. Pleomorphic adenoma was the most common histological type (65.17%). Mucoepidermoid carcinoma and adenoid cystic carcinoma were the most common malignant tumors. Conclusion. It was shown that the peak incidence age of all salivary gland tumors was the third to fifth decades, and malignant tumors mostly occurred in the sixth to eighth decades. Female predominance for all the tumors and slight male predominance in malignant tumors were observed. Pleomorphic adenoma was the most common benign tumor. The most common malignant tumors were mucoepidermoid carcinoma and adenoid cystic carcinoma.